Dynamic Incentive Effects of Heterogeneity in Multi-Stage Promotion Contests - Rudi Stracke; Uwe Sunde (Institute for the Study of Labor (IZA), 2014)
This paper shows that the incentive effects of heterogeneity may be positive rather than negative in dynamic contests with multiple stages. In particular, the well-studied adverse effects of heterogeneity in static interactions are compensated by positive continuation-value and selection effects. Due to these positive dynamic incentive effects of heterogeneity that increase the incentives of relatively more able workers, heterogeneity is unlikely to be as detrimental as commonly perceived for incentives in organizations with multiple hierarchy levels. Heterogeneity of the workforce may even be optimal from the perspective of a firm that provides incentives using a multi-stage promotion contest.
Keywords: M52; J33; 330; incentive provision; multiple-stages; promotion contest; heterogeneity